NUMERICAL STUDY OF DROPLET LENGTH AND BREAKUP TIME FOR GEOMETRY AND FLOW PARAMETERS IN A T-JUNCTION MICROFLUIDICS - P N, Sudheer; Bekal, Chandrakantha; Shetty, Manjunath; Shenoy B, Satish (Journal of Applied Engineering Science, 2026)
Droplet microfluidics finds its application in medical, chemical and biological research as well as in the field of medical device manufacturing. This paper studies the T-junction microfluidics and its parameters, such as droplet length and breakup time, as they vary with the channel width and phase velocities. The study reveals that droplet length rises with an increase in either of the channel width and time taken for breakup reduces and attains a steady value when dispersed phase width is increased. The droplets are smaller in size and form very quickly when the velocity of continuous phase is increased and vice versa. The study can be utilized as a part of a larger study of droplets and their particle encapsulations, and its utilization to generate more efficient and economical medical devices.
Keywords: droplets microfluidics, t-junction, droplets length, droplet breakup